Non-invasive Complementary Therapies in Managing Musculoskeletal Pains and in Preventing Surgery - Pugazhendi, MPT, Sujatha; Rajamani, BHMS, MSc, Priyadarshini; Daniel, MPT, Amalan S.; Pugazhendi, MBBS, MS, Kannan (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Musculoskeletal disorders are disabling diseases which affect work performance, thereby affecting the quality of life of individuals. Pharmacological and surgical management are the most recommended treatments. However, noninvasive physical therapies are said to be effective, for which the evidence is limited. Aim/Purpose: To study the effect of non-invasive physical interventions in preventing surgery among patients recommended for surgery for musculoskeletal complaints, who attended sports and fitness medicine centres in India. Settings: SPARRC (Sports Performance Assessment Research Rehabilitation Counselling) Institute) is a physical therapy centre with 13 branches spread all over India. This Institute practices a combination of manual therapies to treat musculoskeletal complaints. Research Design: Descriptive cohort study involving the review of case records of the patients enrolled from June 2013 to July 2017, followed by the telephone survey of the patients who have completed treatment. Intervention: Combination of physical therapies such as myofascial trigger release with icing, infra-red therapy, pulsed electromagnetic field therapy, stretch release, aqua therapy, taping, and acupuncture were employed to reduce the pain and regain functionalities. Main Outcome Measures: Self-reported pains were measured using visual analogue scale at different levels of therapy—pre and post-therapy and post-rehabilitation. Results: In total, 909 patients were studied, of whom 152 (17%) patients completed the treatment protocol. Majority of patients presented with knee and low-back pain. The reduction in pain due to the treatment protocol in terms of mean VAS score from baseline to post-therapy and baseline to post-rehabilitation was statistically significant (p value = .00). Among those contacted post-rehabilitation, 82 patients remained without surgery, and the median surgery-free time was around two years. Conclusion: Thus the study concluded that non-invasive physical therapies may prevent or postpone surgeries for musculoskeletal complaints.